Replacing post–chest tube removal chest radiographs with clinical assessment in adult thoracic surgery patients: A single-center prospective studyCentral MessagePerspective - Andreea C. Matei, MD, MSc; Awrad Nasralla, MD; Najib Safieddine, MD, FRCSC; Sayf Gazala, MD, FRCSC; Carmine Simone, MD, FRCSC; Negar Ahmadi, MD, MSc, MPH, FRCSC (JTCVS Open)
Objective: The necessity and utility of chest radiographs in the absence of clinical symptoms have been questioned after chest tube removal. This study aimed to evaluate the impact of replacing routine chest radiographs after chest tube removal with clinical observation on outcomes in patients undergoing elective thoracic surgery. Methods: This was a single-center prospective study of adult patients undergoing elective lung resection. Standard chest radiographs after chest tube removal were replaced with a clinical observation protocol for 2 hours after removal. Chest radiographs after chest tube removal were meant to be obtained only for symptomatic patients. The primary outcome was the incidence of adverse events related to this change. Secondary outcomes included changes in clinical management, length of stay, and postoperative complications. Results: A total of 248 patients were included in the study period, and the majority (n = 185, 75%) did not have chest radiographs after chest tube removal. There was no significant difference in the incidence of adverse events or postoperative complications between patients who received chest radiographs and those who did not. Additionally, length of stay was significantly shorter in patients who did not receive chest radiographs (median 2.3 vs 3 days; P < .05). Conclusions: Clinical observation can safely replace routine chest radiographs after chest tube removal in asymptomatic patients undergoing elective thoracic surgery. This approach may lead to shorter hospital stays and reduced healthcare costs without compromising patient safety. The findings support a clinically driven use of postoperative imaging in this patient population, highlighting the importance of individualized patient care.